Three Co(II)-coordination polymers based on 5-tert-butyl isophthalic acid and isomeric Bis(imidazole) ligands: Synthesis, optical and magnetic properties - Arici, Mursel; Yesilel, Okan Zafer; Buyukgungor, Orhan; Yerli, Yusuf (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
Three new Co(II)-coordination polymers, namely {[Co-3(mu(3)-tbip)(mu(4)-tbip)(mu(4)-tbip)(mu 4H2O)(mu-obix)]center dot 3H(2)O}(n) (1), [Co-3(Htbip)(mu-HtbiP)(mu(4)-thiP)(mu(4)-tbip)(H2O)(mu-mbix)](n) (2) and [Co-2(mu(3)-tbiP)(2)(mu-Pbix)](n) (3) (tbip: 5-tert-butyl isophthalate, o, m, pbix: 1,X-bis(imidazol-lylmethyl)benzene, X = 2, 3, 4) were systematically synthesized with H(2)tbip and isomeric bis(imidazole) linkers under hydrothermal conditions to investigate the influence of isomeric ligands on the structural diversity. They were characterized by elemental analysis, IR spectroscopy, single and powder X-ray diffractions. X-ray results showed that complexes 1 and 3 possessed 3D framework while complex 2 was 2D layer. In 1 and 2, trinuclear [Co-3(COO)(6)(OH2)] and [Co-3(COO)(6)] units were connected by tbip ligands to form 2D and 1D structures which were extended to form 3D and 2D structures by neutral ligands, respectively. Complex 3 was mutually interpenetrated each other to form 3D + 3D -> 3D interpenetrated framework with crs/dia-e topology. In 2, tbip ligand displayed new coordination modes. Moreover, thermal, optical and magnetic properties of the complexes were also studied. (C) 2018 Elsevier Ltd. All rights reserved.s
Keywords: 5-tert-Butyl isophthalate; Co(II)-coordination polymer; Semi-flexible bis(imidazole) linkers; Magnetism; METAL-ORGANIC FRAMEWORKS; COORDINATION POLYMERS; CRYSTAL-STRUCTURES; TOPOLOGICAL STRUCTURES; GAS-ADSORPTION; CONSTRUCTION; COPPER(II); SEPARATION; COMPLEXES; DESIGN; Chemistry; Crystallography